HUBUNGAN INTENSITAS PENERANGAN DENGAN KELELAHAN MATA PADA PENGRAJIN BATIK TULIS - Nina Wiyanti; Tri martiana (The Indonesian Journal of Occupational Safety and Health, 2015)
ABSTRACTOne of eye’s health problems that can be experienced by batik artisans are eyestrain. There are many factors that can cause eyestrain, one of them is the intensity of the illumination. This study aimed to analyze the relationship between the intensity of illumination with eyestrain on batik artisans. This type of research is descriptive observational study with cross sectional design. This research was conducted in nine home industry batik which is in the area of Kampung Batik Jetis Sidoarjo. Data obtained by direct measurement, observation, interviews, and see the monument which contains the history of the Jetis batik village. The results showed that the intensity of illumination in some Jetis batik home industry does not reach the standards of the majority of the UNEP (500 lux). The craftsmen who experience eyestrain or not, the amount is balance. Based on the results of the statistical test known that the value of Cramer’s V coefficient is 0.905, which means the intensity of illumination with eyestrain has a very strong relationship level. The conclusion is, the intensity of the light which majority does not reach the standards had a very strong relationship with eyestrain. It is recommended to improve workplace hygiene lighting installation (including lamps), perform color settings and decorations workplace, using natural light as much as possible, and perform eye exams to the eye doctor regularly. Especially if the batik artisan’s eyes look red, watery, and itchy and feeling frequent headaches.Keywords: intensity of illumination, eyestrain